Calculation of Electron Swarm Parameters in Tetrafluoromethane - Salih, Idris H.; Othman, Mohammad M.; Taha, Sherzad A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The electron swarm parameters and electron energy distribution function (EEDF) are necessary, especially on understanding quantitatively plasma phenomena and ionized gases. The EEDF and electron swarm parameters including the reduce effective ionization coefficient (α-η)/N (α and η are the ionization and attachment coefficient, respectively), electron drift velocity, electron mean energy, characteristic energy, density normalized longitudinal diffusion coefficient, and density normalized electron mobility in tetrafluoromethane (CF4) which was analyzed and calculated using the two-term approximation of the Boltzmann equation method at room temperature, over a range of the reduced electric field strength (E/N) between 0.1 and 1000 Td (1Td=10-17 V.cm2), where E is the electric field and N is the gas density of the gas. The calculations required cross-sections of the electron beam, thus published momentum transfer, vibration, electronic excitation, ionization, and attachment cross-sections for CF4 were used, the results of the Boltzmann equation in a good agreement with experimental and theoretical values over the entire range of E/N. In all cases, negative differential conductivity regions were found. It is found that the calculated EEDF closes to Maxwellian distribution and decreases sharply at low E/N. The low energy part of EEDF flats and the high-energy tail of EEDF increases with increase E/N. The EEDF found to be non-Maxwellian when the E/N> 10Td, having energy variations which reflect electron/molecule energy exchange processes. In addition, limiting field strength (E/N)limit has been calculated from the plots of (α-η)/N, for which the ionization exactly balances the electron attachment, which is valid for the analysis of insulation characteristics and application to power equipment.